Eye and muzzle temperatures measured using infrared thermography to assess sheep stress during shearing and foot trimming - Almeida M.D.; Stilwell G.; Guedes C.; Silva S.R. (Innovation for sustainability in sheep and goats, 2019)
The aim of this study was to investigate the infrared thermography (IRT) to measure eye (IRTeye) and muzzle (IRTmuz) temperature to assess stress in sheep during shearing and foot-trimming procedures. IRT temperatures were measured on 89 ewes of two breeds (55 Churra da Terra Quente – CTQ - and 34 Ilede- France – IF). The IRT images were collected before, during and at the end of each procedure. A FLIR infrared camera was used, and IRT images were analyzed using FLIR Tools+ software to determine IRTeye and IRTmuz. All statistical analyses were performed using the JMP software. Data were analyzed considering breed and time of IRT collection as factors. The IRTeye was higher than IRTmuz (37.26 vs. 31.60 ºC, P<0.01, respectively) for both breeds and procedures. The IF ewes show higher temperatures than CTQ for foot-trimming and shearing (37.49 vs. 37.11 ºC, P<0.05; 37.54 vs. 37.13 ºC, P<0.05, respectively). Time of IRT collection presents different values, the lowest (P<0.05) being observed during and the highest before both procedures. In conclusion, IRT was sensitive in obtaining IRTeye and IRTmuz, being a viable indicator of distress and a valuable tool to assess welfare in sheep during shearing and foot trimming.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)